2008
DOI: 10.1111/j.1600-0765.2007.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of epidermal growth factor receptor‐dependent signaling by Porphyromonas gingivalis lipopolysaccharide in life‐expanded human gingival fibroblasts

Abstract: These studies demonstrate that human telomerase-transduced gingival fibroblasts exhibit an extended life span and recapitulate human gingival fibroblasts biology. Moreover, this system has allowed for the first demonstration of lipopolysaccharide down-regulation of epidermal growth factor activated pathways in human gingival fibroblasts and should facilitate the analysis of signaling events relevant to the pathogenesis and treatment of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…It was suggested that this phenomenon is directly related to the fact that both epidermal growth factor and LPS activate the MAPKs to modulate cell proliferation, cell survival, and the release of inflammatory mediators. The observed alterations in EGF signaling caused by P. gingivalis LPS may be mediated by an array of events, including, among other possibilities, the differential recruitment and altered kinetics of activation of upstream mediators in response to LPS and EGF (72). The effect observed here cannot be associated with LPS activity, since no decrease in EGF activity following incubation with LPS-positive ATCC 33277 ⌬ppad or W83 ⌬ppad P. gingivalis mutants was observed.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…It was suggested that this phenomenon is directly related to the fact that both epidermal growth factor and LPS activate the MAPKs to modulate cell proliferation, cell survival, and the release of inflammatory mediators. The observed alterations in EGF signaling caused by P. gingivalis LPS may be mediated by an array of events, including, among other possibilities, the differential recruitment and altered kinetics of activation of upstream mediators in response to LPS and EGF (72). The effect observed here cannot be associated with LPS activity, since no decrease in EGF activity following incubation with LPS-positive ATCC 33277 ⌬ppad or W83 ⌬ppad P. gingivalis mutants was observed.…”
Section: Discussionmentioning
confidence: 45%
“…It has been previously shown that P. gingivalis lipopolysaccharide (LPS) modulates the regenerative effect of EGF via downregulation of EGFR-dependent signaling (72). It was suggested that this phenomenon is directly related to the fact that both epidermal growth factor and LPS activate the MAPKs to modulate cell proliferation, cell survival, and the release of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Independent of the innate host response, periodontal pathogens target and disrupt various host cellular pathways including tissue homeostasis and repair that are of paramount importance to the pathogenesis of periodontal disease (Darveau, ; Pyrc et al., ; Quinchia‐Rios et al., ). Extracellular signal‐related kinases (Erks) are one of the three main families of MAP kinases.…”
Section: Discussionmentioning
confidence: 99%
“…This disrupts the activation of ERK pathway consequently leading to reduced epidermal cell proliferation. Similarly, Pg LPS is known to inhibit EGF‐mediated signalling by reducing the phosphorylation of ERK2 (MAPK1) and other components of the MAPK signalling cascade including ERK1, p38 MAPK and cyclic‐AMP response element binding (CREB) (Quinchia‐Rios et al., ). We identify and demonstrate that miR‐24 and miR‐27a and miR‐30 target MAPK1 and exhibit antagonistic, yet differential expression in diseased obese and non‐obese gingival tissues.…”
Section: Discussionmentioning
confidence: 99%
“…gingipains, fimbriae, and lipopolysaccharide [LPS]) may disturb the EGF signaling pathway. Indeed, in a model of gingival fibroblasts, purified LPS from P. gingivalis led to a loss of activation of secondary signals depending on the presence of EGF, notably ERK1/2 and p38 kinase, with downstream consequences for the phosphorylation of the transcription factor cAMP response element-binding [17]. In addition to LPS and other known virulence factors, one bacterial enzyme, peptidyl arginine deiminase (PADPg), a unique feature from P. gingivalis , is emerging [18].…”
Section: Introductionmentioning
confidence: 99%